2020
DOI: 10.7547/19-143
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Factors Associated with Balance and Falls in Older Adults: A Systematic Review and Clinical Synthesis

Abstract: Background: Despite evidence suggesting that lower-limb related factors may contribute to fall-risk in older adults, lower-limb and footwear influences on fall-risk have not been systematically summarized. This study was undertaken to systematically review the literature related to lower-limb and footwear factors that may increase fall-risk among community-dwelling older adults. To facilitate the transfer of findings to clinical care, the literature was synthesized and used to inform recommendations as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 118 publications
2
14
0
Order By: Relevance
“…Individual studies reported significant improvements ( p < 0.05) in the groups that intervened with OCS at the time of the TUG test [ 28 , 32 , 33 ], Gait Stability Ratio [ 33 ], variables of the center of pressure [ 35 ], Activities-specific Balance Confidence scale [ 32 ], and dynamic balance [ 34 ]. It has been suggested that one of the factors that would cause a deterioration in balance in older adults would be lower functionality of the lower limbs due to a loss of muscle mass and strength, the aging of biomechanical elements of the musculoskeletal system, a decreased range of motion of the ankle, and less elasticity of the foot tissues, which would limit sensory feedback [ 13 ]. Furthermore, poor balance in older adults has been associated with a delay in muscular responses triggered by proprioceptive deficits that are part of the aging process [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual studies reported significant improvements ( p < 0.05) in the groups that intervened with OCS at the time of the TUG test [ 28 , 32 , 33 ], Gait Stability Ratio [ 33 ], variables of the center of pressure [ 35 ], Activities-specific Balance Confidence scale [ 32 ], and dynamic balance [ 34 ]. It has been suggested that one of the factors that would cause a deterioration in balance in older adults would be lower functionality of the lower limbs due to a loss of muscle mass and strength, the aging of biomechanical elements of the musculoskeletal system, a decreased range of motion of the ankle, and less elasticity of the foot tissues, which would limit sensory feedback [ 13 ]. Furthermore, poor balance in older adults has been associated with a delay in muscular responses triggered by proprioceptive deficits that are part of the aging process [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the regular practice of PA has achieved greater diffusion in recent years as a strategy for fall prevention and improving or maintaining the general health of older adults living in the community [ 13 , 14 ] or participating in government programs [ 15 ], which contributes to an active and healthy lifestyle. The strategies to promote active and healthy aging need to be reassessed due to the COVID-19 pandemic to promote the safe practice of PA among older adults, considering, among other measures, practicing social distancing [ 16 , 17 ] or training at home [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal diseases, along with natural age-related sensorimotor decline, affect the lower limbs' soft tissue homeostasis and/or skeletal integrity, resulting in pain [1], muscle loss [2] and functional decline [3,4] along with elevated fall [5,6] and fracture risk [7]. Even though knowledge discovery has been immense during recent decades, the scientific community has been unsuccessful in treating musculoskeletal diseases, and current prevalence, incidence, and socioeconomic burden still impose a significant threat to healthcare systems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated heels have also been found to elicit increased double support time, heel horizontal velocity at heel strike, and toe clearance (19). Additionally, there are two systematic reviews that presented multiple studies that have identified the influence of elevated heels on stability and gait (9,10).…”
Section: Wears Shoes With Heels Higher Than 25 CM (1 In)mentioning
confidence: 99%
“…A 2020 systematic review conducted by members of our research team identified eight factors regarding feet or footwearrelated impairments or functional limitations that may increase older adults' fall risk: (1) Neuropathy and Sensory Impairment, (2) Foot Pain, (3) Foot or Ankle Orthoses, (4) Shoe or Footwear, (5) Foot Deformities, (6) Strength, (7) Range of Motion, and (8) Skin or Changes in Plantar Soft Tissues (9). The Neville et al (9) systematic review reflected findings from the systematic reviews conducted by Aboutorabi et al (10) and Menant et al (11) that identified the association between inappropriate footwear and falls, as well as the systematic review and metaanalysis by Menz et al (12) which concluded that foot pain, hallux valgus, and lesser toe deformity are risk factors for falling. Subsequent to publication of the Neville et al (9) review, James et al (13) summarized changes in the aging foot and podiatric problems which may be more common in older patients based on their review of the literature and described a method for physical examination with a specific focus on the needs of older patients.…”
Section: Introductionmentioning
confidence: 99%